AMBIGUITY OF GENDER IDENTITY IN SHAKESPEARE’S TWELFTH NIGHT - Resneri Daulay (Universitas Putera Batam, 2018)
Gender is often identified with sex and gender, even though they have different concepts. It is associated with men and women who are socially and culturally formed. Understanding about masculine and feminine discourses are formed to identify gender identity which men must behave masculine and women must behave feminine. Taking William Shakespeare’s Twelfth Night play as its object, this study aims to see how gender identity displayed and describe the ambiguity of gender identity that is acted by character in the play. The data which were taken from the play were analyzed by relating them to the secondary data taken from references discussing the gender identity depicted in the play. The study concluded that sex, gender and sexual orientation are something that is fluid, not natural and changing and constructed by social conditions. Changes of the identity can be said changing with the form performativity shown, namely by disguise.